2018
DOI: 10.3892/mmr.2018.9194
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol improves neurological outcome and neuroinflammation following spinal cord injury through enhancing autophagy involving the AMPK/mTOR pathway

Abstract: Resveratrol, a natural phenolic compound, provides neuroprotective effects, however, the specific mechanisms of action remain to be elucidated. The purpose of the present study was to examine the neuroprotective effect of resveratrol on spinal cord injury (SCI) and the potential molecular mechanisms of action. A rat model of SCI was induced using Allen's method, and resveratrol (100 mg/kg) was intraperitoneally injected 1 day following surgery. The recovery of neurological function was assessed using the Basso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 25 publications
1
25
0
Order By: Relevance
“…Similarly, restoring autophagic flux by resveratrol may be a promising approach in the prevention of cellular senescence and amelioration of insulin resistance . Resveratrol was found to exhibit neuroprotective effects by activating AMPK/mTOR‐mediated autophagy in a rat model of spinal cord injury . In clinical trials, resveratrol has been shown to modulate autophagy‐related pathways such as AMPK and SIRT1 …”
Section: Molecular Targets Of Resveratrol In Humansmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, restoring autophagic flux by resveratrol may be a promising approach in the prevention of cellular senescence and amelioration of insulin resistance . Resveratrol was found to exhibit neuroprotective effects by activating AMPK/mTOR‐mediated autophagy in a rat model of spinal cord injury . In clinical trials, resveratrol has been shown to modulate autophagy‐related pathways such as AMPK and SIRT1 …”
Section: Molecular Targets Of Resveratrol In Humansmentioning
confidence: 99%
“…217 Resveratrol was found to exhibit neuroprotective effects by activating AMPK/mTOR-mediated autophagy in a rat model of spinal cord injury. 218 In clinical trials, resveratrol has been shown to modulate autophagy-related pathways such as AMPK and SIRT1. 204 Resveratrol may find utility to lower the toxicity of chemotherapeutic drugs.…”
Section: Molecular Targets Of Resveratrol In Humansmentioning
confidence: 99%
“…Resveratrol can induce apoptosis and inhibit angiogenesis, thereby suppressing tumor growth and metastasis [105]. Importantly, resveratrol induced autophagy in various in vitro and in vivo disease models, by activating AMPK [106][107][108][109]. However, the mechanisms underlying the autophagy-and inflammasome-modulating effects of resveratrol in the context of cancer remain unclear.…”
Section: Effects Of Autophagy-modulating Agents On Inflammasomesmentioning
confidence: 99%
“…Although the pathophysiology of SCI has been continuously investigated, the precise pathogenesis has not yet been fully elucidated. Several studies revealed the pathophysiology of injury, including neuronal inflammation, reactive changes in the glia, oxidative stress, neuronal degeneration and apoptosis (Chen et al, 2018;Lu et al, 2018;Meng et al, 2018). Disturbances in the spinal cord blood flow (SCBF), severely reduced oxygen levels, perfusion defects, hemorrhage, ischemia, and hypoxia have been demonstrated as a focus of post-injury pathophysiological changes of acute SCI (Huo et al, 2019).…”
Section: Introductionmentioning
confidence: 99%